The Bullying Phenomenon and Handling Efforts in Reducing Cases of Bullying: A Systematic Review - Devis Yulia Rohmana; Kartini Estelina; Iskandar Iskandar (Universitas Airlangga, 2020)
Introduction: Bullying is behavior that deliberately wants to dominate, hurt, or get rid of its victims, both directly (physical) or indirectly (verbal). The impact of bullying can cause psychological distress and if left untreated will worsen the victim to the point of committing suicide. This study aims to find out the most appropriate types of interventions that can be implemented to reduce intimidation and prevent the risk of suicide by using systematic reviews based on PRISMA guidelines.Methods: The studies were searched in five databases: Scopus, ScienceDirect, Proquest, Pubmed and CINHL and had to be published from 2014-2019. The articles were identified using the keywords “bullying” AND “intervention”, “anti-bullying program”.Results: 14 articles found were used using this systematic review. The article reviewed mentions that an antibullying program that involves several parties has the benefit of reducing bullying.Conclusion: Several intervention efforts can be used in preventing recurring breaches and can also be used as promotive and preventive efforts in cases of bullying in schools and communities.